International development higher education: looking from the past, looking to the future - Chankseliani, M (Taylor and Francis, 2022)
International development higher education is a distinct space in a vibrant and growing field of higher education studies. This paper examines international development higher education scholarship to highlight its thematic, disciplinary, methodological, and analytical eclecticism. At the heart of international development higher education is the assumption that the world can be made better by the human effort invested in higher education. This paper offers a novel conceptualisation of the ways in which higher education’s contributions to development can be understood. The bulk of the existing literature essentialises higher education’s role in the advancement of human capital and the modernisation of societies. In contrast, anti-essentialist understandings can include various conceptualisations of how higher education can contribute to the realisation of human rights and capabilities to pursue the freedoms people value. A holistic understanding of university contributions to development would encompass all of the essentialist and anti-essentialist, as well as post-foundationalist ways of looking at this important but empirically elusive link. The paper suggests to delink development from ‘international’ and reframe development as ‘glonacal’, thus allowing scholars and practitioners to be less bound by nation-state borders, and more conscious of the local nuance and the global connectedness.